2019
DOI: 10.1530/biosciprocs.1.004
|View full text |Cite
|
Sign up to set email alerts
|

Control of seasonal reproduction in sheep and goats by light and hormones

Abstract: Seasonal variations of reproductive ability have been demonstrated in male and female sheep and goats. For the female, there is a distinct breeding season. Whilst there are large breed differences in the duration of the sexual season, oestrous cycles generally start when daylength is decreasing and end when daylength is increasing. In some breeds, ovulation without oestrus occurs during the non-breeding season. Although males are able to mate all the year round, seasonal variations occur in the weight of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 50 publications
1
9
0
8
Order By: Relevance
“…An essential finding reported here was the marked seasonal variation of LH, FSH, P4, E2, and T4 concentrations in hinds’ blood plasma as described before 39 . Our results have clearly shown that LH concentration in hinds’ plasma was at a similar level during all analyzed seasons, but we did not analyze the preovulatory outflow period.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…An essential finding reported here was the marked seasonal variation of LH, FSH, P4, E2, and T4 concentrations in hinds’ blood plasma as described before 39 . Our results have clearly shown that LH concentration in hinds’ plasma was at a similar level during all analyzed seasons, but we did not analyze the preovulatory outflow period.…”
Section: Discussionsupporting
confidence: 74%
“…Yuthasastrakosol et al 40 noted the high LH levels in anestrus in ewes, and they suggested an association of these values with the increase in P4 levels. Low levels of P4 during anestrus in goats and high levels of P4 in the luteal phase in sheep, during the middle of reproductive season, were observed by Thimonier 39 . In turn, Li et al 9 did not observe a luteal P4 peak in sheep during anestrus.…”
Section: Discussionmentioning
confidence: 91%
“…In some small ruminants, such as goats and sheep, animals restrict their breeding season to a short period of the year, allowing births to occur during favourable environmental temperatures and high availability of pastures (Bronson, ). The reproductive seasonality in goats and sheep is mainly modulated by changes in the day length; natural decreasing or artificial short days stimulate ovulations, whereas natural increasing or artificial long days inhibit it (Thimonier, ). In goats from subtropical regions, ovulation is always stimulated during artificial short days (10 hr light/day) when exposed to alternations between 3 months of long and 3 months of short days (Duarte, Nava‐Hernández, Malpaux, & Delgadillo, ).…”
Section: Introductionmentioning
confidence: 99%
“…The GnRH pulse generator is a critical mechanism that underlies cyclical changes in the HPG axis activity that helps drive the female reproductive cycle as well as male reproductive function, which is not cyclic, although it may undergo seasonal changes (57,58). Pulse generation appears to be an integration point for various inputs and mechanisms involved in the role of CNS in regulating fertility, but its composition and mechanisms underlying coordinated production of GnRH pulses remain poorly understood.…”
Section: Gnrh Pulse Generator-comprehensive Overviewmentioning
confidence: 99%